Professional Skills Demanded by the Peruvian Labour Market - Gutiérrez-Villaverde, Herberth Eduardo (2015)
This paper describes the skills most required among  professionals within various career paths by leading companies in the Peruvian market, which advertise staffing positions via the weekly magazine Aptitus, part of the newspaper El Comercio,  and  through  other media outlets. This database was created by accumulating results from more than 5,700 job advertisements between 2012 and 2013. By applying multivariate techniques, the job market was identified and  the most demanded competencies within professional careers were defi ed.